2014
DOI: 10.1063/1.4866874
|View full text |Cite
|
Sign up to set email alerts
|

Serrated flow behaviors of a Zr-based bulk metallic glass by nanoindentation

Abstract: Shock compression response of a Zr-based bulk metallic glass up to 110 GPa J. Appl. Phys. 108, 083537 (2010); 10.1063/1.3501044 Temperature-dependent shear band dynamics in a Zr-based bulk metallic glass Appl. Phys. Lett. 96, 061901 (2010); 10.1063/1.3309686Effect of high strain rates on peak stress in a Zr-based bulk metallic glass J. Appl. Phys.Instrumented nanoindentation tests were used to investigate the mechanical properties of Zr 52.5 Cu 17.9 Ni 14.6 Al 10 Ti 5 bulk metallic glass. The corresponding loa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 29 publications
3
12
0
Order By: Relevance
“…2(a) show that the size of the serrations increases while the number of the serrations decreases with the increase of h. The similar phenomenon was also found by Yang 14 on Au-based BMG and Cheng 15 on Zr-based BMG. To confirm the phenomenon at greater h, the nanoindentation tests with h final = 1000 nm were performed, as seen in Fig.…”
Section: Resultssupporting
confidence: 64%
“…2(a) show that the size of the serrations increases while the number of the serrations decreases with the increase of h. The similar phenomenon was also found by Yang 14 on Au-based BMG and Cheng 15 on Zr-based BMG. To confirm the phenomenon at greater h, the nanoindentation tests with h final = 1000 nm were performed, as seen in Fig.…”
Section: Resultssupporting
confidence: 64%
“…(5), the free volumes grow during the plastic deformation, which has been verified by experiments [20,21,[24][25][26] and modelings [23]. Thus, the annihilation rate is smaller than the creation rate upon deformation.…”
Section: Discussionmentioning
confidence: 72%
“…Recently, Ke et al reported [26] that the Zr 46.75 Ti 8.25 Cu 7.5 Ni 10 Be 27.5 BMG exhibited volume dilatation of up to 0.2% after compressive creep of the as-cast sample at a yield stress of 80%, and this phenomenon is attributed to the generation of a great amount of free volumes. The increased free volumes make the Young's modulus of the glass matrix decrease [20,24,25], resulting in the Young's modulus of the glass matrix and dendrites being approaching, since the crystalline dendrites have a lower Young's modulus than the glass matrix. The aim of this study is to investigate the contribution of matching the Young's modulus between the glass and dendrite phases to the plasticity of in-situ dendrite-reinforced MGMCs.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, Xue et al [12] reported a positive strain rate dependence of the hardness and ascribed this correlation to the stronger strain rate softening effect under lower strain rates. There are also analogous inconsistent results, but the underlying mechanism has been rarely shed light on [13][14][15][16][17]. In addition, Bhattacharyya et al [6] demonstrated a lower strain rate sensitivity of the hardness under a higher peak-load, but the results of Ma et al [17,18] showed a much more positive rate sensitivity when the peak-load increased by 1 order of magnitude.…”
mentioning
confidence: 65%